Adults with intellectual disabilities' lived experiences of wellbeing and the internet: a descriptive phenomenological study. Issue 4 (22nd April 2022) - Hebblewhite, Gillian; Hutchinson, Nick; Galvin, Kathleen
Abstract: While internet use continues to increase amongst the general population, in comparison, adults with intellectual disabilities are still less likely to access the Internet and benefit from the opportunities it can offer. Non-intellectual disability perspectives and assumptions, which often view the Internet as a risk for those with intellectual disabilities, are considered over the everyday lived online and well-being experiences of adults with intellectual disabilities. In response, this study interviewed 8 participants with intellectual disabilities using a descriptive phenomenological approach. Seven constituents emerged: internet as a mirror; internet enables visibility and invisibility; internet as liberating; internet meets unmet needs; internet creates an active decision maker and expert; internet as friend and foe; and, the body connects to, and disconnects from, the Internet. The findings gave rise to new perspectives, recommendations, and adds to the existing literature on how to support adults with intellectual disabilities' enjoyable, safe and independent internet use. Points of interest: Participants with intellectual disabilities described feeling unsafe and restricted in their offline lives, but online they often felt safer and that they could do anything. Participants did not view their intellectual disability positively. Online they could keep their disabilities hidden from others, creating a variety of identities (creative, strong, protective and helpful) that they felt represented them more accurately. When the internet was described as a positive resource in life, this was linked to a sense of well-being with an identity emphasis. Additionally, findings point to examples of well-being in spatial, embodied, mood, sense of belonging with others and temporal ways. This study highlights how danger was negotiated by people with intellectual disabilities in similar ways to dangers in everyday life and how these skills are transferable to offline and online worlds.